DEVELOPMENT OF LITERARY PRONUNCIATION IN PRIMARY EDUCATION BY TEACHING PUPILS THE CORRECT PRONUNCIATION IN MOTHER TONGUE LESSONS - Atamurodova Gulnora Shermurodovna; Uzoqova Durdona Muratali qizi (Sciental Journals Publishing, 2025)
The article aims to teach students literary pronunciation by forming correct pronunciation skills in native language lessons of primary education. As well as the development of teaching tasks and exercises that form the correct pronunciation skills, their application in practice.
Keywords: Literary pronunciation, speech sounds, exercise and assignment, program and textbook.